Cervical degenerative conditions - Vialle, Luiz Roberto; Riew, K. Daniel; Ito, Manabu (AOSpine masters series, 2015)
This third volume in the AOSpine Masters Series covers the most common operative techniques for treating degenerative cervical conditions. The book provides expert guidance to help clinicians make the right treatment decisions and provide the best care for their patients. Chapter topics range from Laminectomy and Fusion for Cervical Spondylotic Myelopathy to Complications on Anterior Surgery: VA Injury, Esophageal Perforation, and Dysphagia.Key Features:Synthesizes the best available evidence and consensus expert advice on each operative technique for degenerative cervical conditions, leading